2016
DOI: 10.1084/jem.20151724
|View full text |Cite
|
Sign up to set email alerts
|

B cell IFN-γ receptor signaling promotes autoimmune germinal centers via cell-intrinsic induction of BCL-6

Abstract: Jackson et al. propose a role for B cell–intrinsic IFN-γ receptor signaling in spontaneous germinal center activation and autoantibody production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
209
2
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 187 publications
(232 citation statements)
references
References 50 publications
(91 reference statements)
20
209
2
1
Order By: Relevance
“…Others have previously reported different requirements for GC formation in spontaneous autoimmunity versus deliberate immunization, with IFN-γR needed for the former but not the latter event (30,31). These observations, together with another observation that TLR7 expression in B cells is needed for GC appearance in spontaneous autoimmunity (39), are in line with our findings with respect to T-bet + ABCs, since ABC formation depends on IFN-γ and TLR7 signaling in B cells (11).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Others have previously reported different requirements for GC formation in spontaneous autoimmunity versus deliberate immunization, with IFN-γR needed for the former but not the latter event (30,31). These observations, together with another observation that TLR7 expression in B cells is needed for GC appearance in spontaneous autoimmunity (39), are in line with our findings with respect to T-bet + ABCs, since ABC formation depends on IFN-γ and TLR7 signaling in B cells (11).…”
Section: Discussionsupporting
confidence: 92%
“…These observations, together with another observation that TLR7 expression in B cells is needed for GC appearance in spontaneous autoimmunity (39), are in line with our findings with respect to T-bet + ABCs, since ABC formation depends on IFN-γ and TLR7 signaling in B cells (11). However, the results of some others differ from those reported here in one respect, since some, but not all other studies found that T-bet expression in B cells was not required for spontaneous GC formation (30,31).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Autoantibody titers were measured by ELISA as previously described (59). Briefly, 96-well Immuno plates (Nunc) were precoated overnight at 4°C with calf thymus dsDNA (100 μg/ml; MilliporeSigma, D3664-5X2MG) or Sm/RNP (5 μg/ml; Arotec Diagnostic Limited, ATR01-10).…”
Section: Mice Dock8mentioning
confidence: 99%